COVID-19 in Sudan: Impacts on Production, Household Income & Food Systems - Abay, Kibrom; Breisinger, Clemens; Ibrahim, Hosam; Raouf, Mariam (2021)
Prepared by Kibrom Abay, Clemens Breisinger, Hosam Ibrahim and Mariam Raouf International Food Policy Research Institute Last updated: 28 July 2020